Considerations for culturally informed leadership : moving toward the future - Guthrie, Kathy L.; Pierre, Darren E. (Emerald Publishing Limited, 2025)
Considerations for Culturally Informed Leadership: Moving Toward the Future explores the dynamic process of leadership across diverse cultural landscapes. This book invites readers to embark on a journey of self-discovery and reflection, encouraging them to see themselves as learners, engagers, and connectors in a global context. Each chapter begins with a framing section to set the stage for learning, followed by stopping points for readers to pause and reflect on their insights. Thought-provoking questions and discussion prompts at the end of each chapter foster meaningful conversations and deeper understanding. Additionally, practical activities are designed to elevate leadership skills, taking learning to the next level. Whether readers are college or high school students, part of a student organization, or pursuing individual learning, this book offers valuable opportunities to enhance leadership practice in a classroom setting and beyond. It aims to unlock the potential of culturally informed leaders and make a lasting impact in today's interconnected world.
Includes index.
Keywords: Intercultural communication.; Leadership.; Business & Economics -- Leadership.; Management: leadership and motivation.; elektronické knihy; electronic books